Studi Literarure: Konsep Psikologis Perawat di Masa Pandemi Covid-19 - Andria Pragholapati; Eni Hidayati (Jurnal Keperawatan Komplementer Holistic e-ISSN 2988-3709 (online), 2023)
The Covid-19 pandemic is a major health crisis affecting the World today, with over 178,202,610 confirmed cases and 3,865,738 deaths from this disease having been reported to date. The widespread Covid-19 outbreak is associated with adverse mental health consequences including that of nurses. With this in mind, the existing literature on nurse psychology in the Covid-19 pandemic was retrieved through a literature search from the Google Scholar database, PubMed, Sciencedirect, Garuda, WHO, and KEMENKES. Published articles are classified according to the overall theme and are summarized. The available literature emerges from only a few of the countries affected, and may not reflect the experiences of people living in other parts of the world. In conclusion, nurses' psychological problems are a common response to the COVID-19 pandemic. There is a need for more representative research from other affected countries, especially in vulnerable populations.